Resilient Modulus Testing of Materials from Mn/ROAD, Phase 1. - Berg, Richard L.; Bigl, Susan R.; Stark, Jeffrey A.; Durell, Glenn D. (1996)
The U.S. Army Cold Regions Research and Engineering Laboratory (CRREL) conducted resilient modulus tests on materials from the Mn/ROAD test site for the Minnesota Department of Transportation. Materials tested included samples of the lean clay subgrade at the site and the two extreme grades of base designed specifically for Mn/ROAD. Some specimens were tested in both frozen and subsequently 'thawed' conditions; others were tested at room temperature without ever having been frozen. Researchers performed linear regression analysis on the data to develop equations that predict frozen modulus based on unfrozen water content and unfrozen modulus based on stress, degree of saturation and density. We also reanalyzed data from two previously tested materials. CRREL can use the study's equations in the Mechanistic Pavement Design and Evaluation Procedure under development at CRREL to predict estimated damage in some Mn/ROAD test sections.